UNIT 13.28 Using PSEA‐Quant for Protein Set Enrichment Analysis of Quantitative Mass Spectrometry‐Based Proteomics. Issue 1 (24th March 2016) - Lavallée‐Adam, Mathieu; Yates, John R.
Abstract : PSEA‐Quant analyzes quantitative mass spectrometry–based proteomics datasets to identify enrichments of annotations contained in repositories such as the Gene Ontology and Molecular Signature databases. It allows users to identify the annotations that are significantly enriched for reproducibly quantified high abundance proteins. PSEA‐Quant is available on the Web and as a command‐line tool. It is compatible with all label‐free and isotopic labeling‐based quantitative proteomics methods. This protocol describes how to use PSEA‐Quant and interpret its output. The importance of each parameter as well as troubleshooting approaches are also discussed. © 2016 by John Wiley & Sons, Inc.